High-Throughput Satellite Precoding Algorithm Based on Non-Ideal Channel State Information - Yingzhe DOU; Guanchang XUE; Mingchuan YANG (天地一体化信息网络)
In order to suppress co-channel interference caused by frequency reuse, high-throughput satellite communication systems have begun to study ground interference suppression technologies, including multi-user detection technology applied in the reverse link and precoding technology applied in the forward link.A forward link model was established that took into account the eff ects of free space loss, rain attenuation, and beam gain.Based on the non-ideal channel state information model, the minimum mean square error precoding algorithm was improved, and an improved minimum mean square error precoding algorithm suitable for non-ideal channel state information was proposed.The satellite precoding algorithm considered adopted a more accurate channel model with irrational channel information, and incorporated the non-ideal channel state information into the precoding algorithm and eliminated it.The simulation results showed that the high-throughput satellite precoding algorithm could signifi cantly improved the throughput of the system under the condition of non-ideal channel state information, and also improved the robustness of the system.